Regulatory Effect of 1,25(OH)2D3 on TGF-β1 and miR-130b Expression in Streptozotocin-Induced Diabetic Nephropathy in Rats - Yuetong Liu; Ye Yang; Qin Wang; Apaer Kahaer; Jiyun Zhang; Jing Liao; Mairemugu Abudureyimu; Reyila Yahefu; Jing Qi; Lei Zhao; Jun Zhu (International Journal of Endocrinology)
Objective. To investigate the role of microRNA-130b in 1,25(OH)2D3 mediated improvement of renal fibrosis via transforming growth factor-beta 1 in a rat model of diabetic nephropathy (DN). Methods. DN was induced in 30 rats by intraperitoneal injection of streptozotocin. These rats were randomly allocated to the DN group, TGF-β1 overexpression group (in situ injection of TGF-β1 lentivirus to kidney tissues), and TGF-β1 siRNA group (in situ injection of TGF-β1 siRNA lentivirus to kidney tissues). Rats with different expression levels of TGF-β1 were administered 1,25(OH)2D3 (0.03 μg/kg/d) or peanut oil as control. DN rats were treated only with peanut oil. All rats were randomly divided into five groups (n = 6 per group): TGF-β1 overexpression + oil, TGF-β1 overexpression + 1,25(OH)2D3, TGF-β1 siRNA + oil, TGF-β1 siRNA + 1,25(OH)2D3, and DN + oil groups. After 37 days, kidney samples were collected and the expression of TGF-β1 and miR-130b was determined by real-time PCR, western blotting, and immunohistochemistry. Hematoxylin and eosin staining and Masson staining were used to evaluate kidney morphological and fibrogenic changes. Differences were determined using ANOVA and Student’s t-test. Results. RT-PCR, western blotting, and immunohistochemistry revealed that interference of TGF-β1 significantly decreased mRNA and protein levels of TGF-β1 in renal tissues of DN rats compared to those in renal tissues of rats overexpressing TGF-β1 (p<0.05). Histological analysis showed that upregulated TGF-β1 led to disorganized kidney structure and severe kidney fibrosis. The expression of miR-130b was significantly lowered upon lentivirus-mediated overexpression of TGF-β1 than upon downregulation of TGF-β1 (p<0.05). Treatment with 1,25(OH)2D3 led to a significant reduction of TGF-β1 at the mRNA and protein levels (both p<0.05), improvement of renal structure and fibrosis, and an increase in miR-130b expression (p<0.05). Conclusion. TGF-β1 can decrease the expression of miR-130b in kidney tissues of DN rats. Moreover, miR-130b may be involved in the protective effect of 1,25(OH)2D3 on renal fibrosis via TGF-β1.